2009
DOI: 10.1029/2008jd011040
|View full text |Cite
|
Sign up to set email alerts
|

Cirrus observations in the tropical tropopause layer over the western Pacific

Abstract: A polarization lidar was continuously operated aboard the research vessel Mirai in the tropical western Pacific over three northern winters: at 2.0°N, 138.0°E during November and December 2001; at 2.0°N, 138.5°E during November and December 2002; and at 7.5°N, 134.0°E during December 2004 and January 2005. Intensive radiosonde soundings were made from the vessel at 3‐h intervals during all three campaigns. The mechanisms that underlie the observed variations in cirrus in the tropical tropopause layer (TTL) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 79 publications
5
75
0
Order By: Relevance
“…There is now evidence from several studies (Boehm and Verlinde, 2000;Immler et al, 2008;Fujiwara et al, 2009;Virts et al, 2010;Flury et al, 2012) that there is a correlation between cold anomalies in the TTL and cirrus clouds. From recent studies on cirrus clouds in the TTL using the lidar in space onboard CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation), the vertical motions in the regions of cirrus cloud occurrence were estimated (Virts et al, 2010).…”
Section: Large-scale Dynamicsmentioning
confidence: 99%
“…There is now evidence from several studies (Boehm and Verlinde, 2000;Immler et al, 2008;Fujiwara et al, 2009;Virts et al, 2010;Flury et al, 2012) that there is a correlation between cold anomalies in the TTL and cirrus clouds. From recent studies on cirrus clouds in the TTL using the lidar in space onboard CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation), the vertical motions in the regions of cirrus cloud occurrence were estimated (Virts et al, 2010).…”
Section: Large-scale Dynamicsmentioning
confidence: 99%
“…According to Fig. 3 of Fujiwara et al (2009), cirrus clouds were observed at around the 355 K potential temperature level (about 15.5 km height) when the second observation of this match was made. The cirrus clouds may have resulted from dehydration of the match air mass shown in Fig.…”
Section: Case 2: Dehydratedmentioning
confidence: 99%
“…Because the default soundings in previous SOWER campaigns did not include any sensors for particles, we could not estimate the total water content in which the air mass has ice particles. In addition, for the campaign region and period (i.e., over the western Pacific in the boreal winter), cirrus clouds are common in the TTL; Shibata et al, 2007;Fujiwara et al, 2009;Massie et al, 2010;Yang et al, 2010;Inai et al, 2012;Shibata et al, 2012). If we could observe ice particles and measure their concentration and size distribution, we could estimate their growth rate under the assumption that a critical relative humidity leads to the initiation of ice nucleation, using the same technique as that employed to estimate the efficiency of dehydration (Sect.…”
Section: Lack Of Dehydrated Cases Near the Cold Pointmentioning
confidence: 99%
“…The variability of TTL clouds depends on cloud microphysics , cloud dynamics (Boehm et al 1999), and large-scale dynamics (Fujiwara et al 2009). On synoptic to subseasonal time scales, equatorial Kelvin waves are one of the most influential disturbances in the TTL (Suzuki and Shiotani 2008;Suzuki et al 2010), significantly affecting the cirrus variability there (Boehm and Verlinde 2000;Immler et al 2008;Fujiwara et al 2009). …”
Section: Introductionmentioning
confidence: 99%